G216(P) Audit of compliance with a guideline for a novel method of preparing breast milk fortifier. (12th March 2018) - King, C; Clark, S
Abstract : Background: Some clinicians suspect that breast milk fortifier may increase risk of necrotising enterocolitis in preterm babies 1 although there is no evidence for this. 2 However there is risk of contamination of breastmilk during fortification, in addition vigorous shaking risks damage to delicate immunological components, and storage for longer than 12 hours leads to coalescing of milk fat globules 3 with reduced surface area for digestion. In 2012 a guideline using a novel method to prepare fortified breastmilk was written to address these concerns; it combed several practices to ensure milk safety. Fortifier is dissolved in 3 ml of breastmilk at the time of preparation to avoid the need for shaking. The concentrate is then used to accurately prepare low volume fortified milk precluding the need for storage over 12 hours. Each step is carried out using aseptic handling. Aims: To audit compliance with this novel method of fortification within a tertiary neonatal unit. Methods: Approval was granted by the local audit committee. The guideline was evaluated by observation of 40 separate preparations of fortified breastmilk during 2 weeks in 2016. All fortification was carried out in the nursery as the unit has no milk kitchen. Seventeen steps were identified and compliance noted for each. Four steps around labelling, 7 around aseptic technique, and 6 around handling. Results: Compliance achieved, ffor labelling 84% of time, aseptic technique 60% and handling 83%.Non-compliance around handling was most common when fortifier was added to large volumes of breastmilk, leading to vigorous shaking of milk to dissolve powder. Conclusion: Non-compliance with aseptic techniques when preparing fortified breast milk is high. This needs to be addressed with ongoing nurse education around the potential risks to milk quality. References: . Sullivan S, Schanler RJ, Kim JH, et al. J Pediatr2010:156:562–567. . Embleton NE, King C, Jarvis C, et al. Breastfeeding Medicine 2013:8(4):421. . Takahashi K, Mizuno K, Itabashi K. Am J Perinatol2012;29:283–288.